Unraveling the relationship between trade openness, economic growth, and financial development in Nigeria - Esther Olayinka Atoyebi; Isiaq Olasunkanmi Oseni; Jimoh Sina Ogede; Soliu Bidemi Adegboyega (Journal of Enterprise and Development (JED), 2024)
Purpose — This study examines the impact of trade liberalization and economic growth on financial development and suggests policies to enhance financial stability.Method — The study utilizes an Autoregressive Distributed Lag Model to analyze the presence of co-movement within the context of trade openness and economic growth on financial development in Nigeria. Additionally, the technique allows for a dynamic assessment of the short and long term.Result — Our findings for Nigeria spanning from 1990 to 2021 demonstrate a positive long-term relationship between trade openness and financial expansion, while economic growth has a negative short-term impact on financial expansion.Contribution — This study contributes to the frontier of knowledge by uncovering the interplay among Nigeria's trade openness, economic prosperity, and financial development, which has been overlooked. Additionally, it offers insights into the specific dynamics and mechanisms operating within the Nigerian context by scrutinizing relevant economic indicators.